Urban climate change adaptation as social learning: Exploring the process and politics - and Fisher, Susannah; Dodman, David (Environmental Policy and Governance, 2019)
Responses to climate change that build on adaptive natural resource management conceptualise social learning processes as having the potential to form a key component of climate adaptation. Social learning processes represent a way of managing the inherent uncertainties and interconnectedness of adaptation issues through ongoing learning, iterative reflection, and change of responses over time. Although the theoretical case is emerging for social learning as adaptation, there is limited empirical evidence of how these processes play out as local governments engage in urban adaptation planning. This paper starts to address this gap by examining social learning processes in two cities in India. We show how the social learning processes interact with complex governance contexts in the two cities and how evidence of outcomes is emerging across individuals, networks, and systems. We go on to argue that there are several areas of social learning that need further theorisation to support its application in the urban context. First, theories of social learning need to allow for unequal power relationships to continue to shape learning processes and take into account structural and historical dynamics as well as relational forms of power. Second, the way that scale is understood needs to be reopened as a point of analysis to understand how scalar concepts are used by actors to frame and locate problems and solutions rather than being understood as fixed and immutable.
Keywords: Climate change; India; Social learning; governance; urban planning